Jamestown (Sloop of war) journal - Jamestown (Sloop of war)
Journal kept by an unknown medical officer aboard the U.S. sloop of war Jamestown on a mission to protect commerce from Confederate privateers in the Pacific. Describes a cruise around the Cape of Good Hope to Japan, gives details about daily life in Japan, and mentions the battle of Shimonoseki-shi involving the U.S. sloop of war Wyoming and the Japanese fleet (Kaigun).
Typewritten transcript is also available.
Typewritten transcript, in part.
Collection material in English.
Keywords: Japan. -- Kaigun; United States. -- Navy -- Cruises; United States. -- Navy -- History -- Civil War, 1861-1865.; United States. -- Navy -- Medical care; Wyoming (Screw sloop); Privateering -- Confederate States of America; Japan -- Description and travel; Japan -- History, Naval; Shimonoseki-shi (Japan) -- History; United States -- History -- Civil War, 1861-1865 -- Naval operations; United States -- History, Naval